SYMBOLIC COMMUNICATION IN MITONI RITUAL AS A MEDIUM OF DA'WAH AND INTERACTION WITH GLOBAL CIVILIZATION IN SINAR MULYO VILLAGE, PULAU PANGGUNG DISTRICT, TANGGAMUS REGENCY - zaky faiz, achmad (Jurnal Komunikasi Islam dan Kehumasan (JKPI), 2024)
This research aims to examine symbolic communication in the Mitoni ritual in Sinar Mulyo Village, Pulau Panggung Subdistrict, Tanggamus Regency, as well as its role as a medium for da'wah and interaction with global civilization. The Mitoni ritual, which is a seven-month tradition in Javanese culture, is rich in symbolism that reflects spiritual and social values. The method used in this research is qualitative with a semiotic analysis approach to understand the meaning of symbols contained in the Mitoni procession, such as offerings, prayers, and other rituals. The results show that the symbols in the Mitoni ritual function as an effective means of delivering da'wah messages to the community, educating them about religious teachings, and strengthening family and togetherness values. In addition, this study reveals that the Mitoni ritual also acts as a bridge that connects local culture with global civilization, creating intercultural dialogue that enriches people's understanding of diversity. Through this interaction, the Mitoni tradition not only maintains local cultural identity but also contributes to strengthening universal values in the context of globalization. This research is expected to provide insight into the importance of maintaining tradition in the process of da'wah and interaction with global civilization, as well as highlighting the role of local culture in shaping da'wah narratives that are relevant in the modern era.